Residual strength prediction of X80 steel pipelines containing group corrosion defects. (15th April 2023) - Zhou, Rui; Gu, Xiaoting; Luo, Xi
Abstract: As subsea oil and gas pipelines are corroded by moisture, soil, and other external factors, their surfaces develop groups of corrosion defects, which are prone to stress concentration and affect the residual strength of the pipeline. To this end, a finite element (FE) model of an X80 pipeline containing group corrosion defects is established here using ABAQUS. Considering the influence of various defect sizes on the residual strength of the pipe, 46 sets of failure data for group corrosion pipes with different geometries and 364 sets of maximum von Mises stresses versus internal pressure for different operating conditions were obtained. The accuracy of the FE model was verified using burst tests. The residual strength prediction model of the pipes was obtained by 1stopt software. The results show that the key factor affecting the residual strength of pipes containing group corrosion defects is the depth of the deepest defect and the strength of the interaction between the group corrosion defects. Based on the DNVRP-F101 standard, a more accurate method for calculating the failure pressure of group corrosion pipes was obtained by introducing correction factors. The results of this study can provide theoretical support for the safe management of group corrosion X80 pipelines. Highlights: A finite element model of X80 steel pipe containing group corrosion defects is made. Failure mechanism is explored to derive the failure law of X80 pipes. Sensitivity analysis of each parameter was carried out to investigate the effect of group corrosion defect parameters. The size of the depth of the deepest defect and the strength of interaction between defects mainly affect the residual strength. An empirical model for the prediction of the residual strength of group corrosion defective pipes was developed.